Knowledge, Attitudes and Practices Relevant to Malaria Control in Remote Island Populations of Manus, Papua New Guinea - Ataka, Yuji (The Japanese Society of Tropical Medicine, 2011)
A community-based cross-sectional survey of 262 participants in four island communities of Manus, Papua New Guinea was conducted using a structured questionnaire to examine possible factors of malaria prevalence, including education experiences, knowledge, attitudes, and preventive behaviors, in relation to antimalarial antibody titers. Bivariate and multivariate analyses revealed that micro-environmental conditions caused inter-community differences in malaria prevalence. Ninety-nine percent of the subject villagers recognized mosquito bites as a cause of malaria transmission, which explains the high possession rate of bednets. There was a significant correlation between malaria education experience at schools and knowledge (p < 0.01) and between knowledge and bednet use (p < 0.05). However, regular bednet users were only 35% of the total, due primarily to feelings of discomfort, heat, and stuffiness inside the bednet. Villagers’ behavior of consulting an aid post orderly (APO) in case of high fever significantly lowered the titer level (p < 0.05), while their bednet use did not. This unexpected result was attributable to inappropriate bednet use and to daily living patterns, including both subsistence and social activities. We conclude that information regarding lifestyles and attitudes toward bednet use as well as malaria education experience at schools are particularly important for practical malaria prevention.